2016
DOI: 10.2174/1573403x12666160606121458
|View full text |Cite
|
Sign up to set email alerts
|

Phase 4 Studies in Heart Failure - What is Done and What is Needed?

Abstract: Congestive heart failure (CHF) therapeutics is generated through a well-described evidence generating process. Phases 1 – 3 of this process are required prior to approval and widespread clinical use. Phase 3 in almost all cases is a methodologically sound randomized controlled trial (RCT). After this phase it is generally accepted that the treatment has a significant, independent and prognostically beneficial effect on the pathophysiological process. A major criticism of RCTs is the population to whom the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 154 publications
0
22
0
Order By: Relevance
“…But in all developed health systems it is premature to invest public resources to understand variations in established observations that do not meet robust requirements of need, especially cost-efficiency. We accept differentials exist in phase 1-3 trials that assume largely private capital, so this argument is largely for phase 4 trials or post translational observations[99-102]. The observations presently is “the cost efficiency of using unimodal risk stratification of CAD within health clusters that serve a multiethnic patient population with varying stages of epidemiological transition based on findings and guidelines from homogenous populations”.…”
Section: Health Clusters and Cost Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…But in all developed health systems it is premature to invest public resources to understand variations in established observations that do not meet robust requirements of need, especially cost-efficiency. We accept differentials exist in phase 1-3 trials that assume largely private capital, so this argument is largely for phase 4 trials or post translational observations[99-102]. The observations presently is “the cost efficiency of using unimodal risk stratification of CAD within health clusters that serve a multiethnic patient population with varying stages of epidemiological transition based on findings and guidelines from homogenous populations”.…”
Section: Health Clusters and Cost Efficacymentioning
confidence: 99%
“…The primary focus are delivery models and cost-efficiency across established health service Taxonomy domains. Nesting this question within larger studies could also broaden the funding appeal[102-105].…”
Section: Health Clusters and Cost Efficacymentioning
confidence: 99%
“…Phase 4 studies have indicated that acting on clinical trial‐derived evidence does not achieve the expected outcomes unless the findings have been validated at the community level . In organised programs with this aim, the art of medical practice becomes evident when assessing non‐phenotypic factors such as rapport, compliance, trust, satisfaction, behavioural change, and personal psychology.…”
Section: The Importance Of a Patient's Cultural Background For Medicamentioning
confidence: 99%
“…Western health practice is built on scientific evidence about the known, rationalising or debating the uncertain, and clarifying by investigation the unknown. Increasingly heterogeneous patient encounters challenge relying only on scientific evidence about the knowns, as conventional evidence gathering rarely focuses on translational elements (phase 4 clinical research) . New approaches are therefore emerging, such as standardising, coding and classifying heterogeneity (eg, taxonomies), broadening the evidence base, and developing local solutions based on post‐trial evidence …”
mentioning
confidence: 99%
“…CMR can similarly detail CR in CRI. As there are other determinants of LVH beyond hypertension including calcium-phosphate balance, this method can inform the adequacy for RRT [ 205 - 213 ]. Impairment in strain rates from all fibers, which go onto correlates with outcomes, is noted in early CRI and hemodialysis [ 210 , 211 ].…”
Section: Comorbidity Assessment With Cmrmentioning
confidence: 99%